Aromatic Amino Acids: Phenylalanine and Tyrosine in Patients with Hypertension and Coronary Artery Disease - A. V. Krivova; M. V. Kozhevnikova; E. O. Korobkova; V. Yu. Zektser; E. A. Zheleznykh; А. A. Ageev; N. E. Moskaleva; A. V. Kukharenko; S. A. Appolonova; Yu. N. Belenkov (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate changes in the profile of aromatic amino acids (AAA) in patients with cardiovascular diseases (CVD): hypertension and coronary artery disease (CАD) in comparison with healthy study participants.Material and methods. One hundred and thirty-one participants were included in the study: 58 participants were included in the hypertension group, 46 in the CАD group, and 27 participants without signs of CVD in the control group. We used ultrahigh-performance liquid chromatography in combination with a triple quadrupole analyzer to measure plasma AAA: phenylalanine and tyrosine (Phe, Tyr) in all study participants. The association of AAA with biochemical blood test parameters, echocardiography (EchoCG) parameters, blood pressure level and clinical characteristics was analyzed.Results. A statistically significant difference in the level of concentration of Phe and Tyr was revealed (p=0,002 and p=0,024, respectively), comparing the three groups. Post-hoc analysis showed differences in the circulating level of both amino acids in patients with CAD vs the control group (Phe p=0,008 and Tyr p=0,020). Also a statistically significant difference in the level of Phe of the hypertension and CАD groups (p=0,017) was found. A negative correlation of low-density lipoproteins (LDL) with the level of Phe (r=-0,685, p<0,05) and Tyr (r=-0,583, p<0,05), as well as the level of Phe with total cholesterol (r=-0,461, p<0,05) was found in the group without CVD. In the hypertension group, only a weak positive correlation was found between very low-density lipoproteins and AAA levels (Phe r=0,326 and Tyr r=0,365, p<0,05), while in patients with CAD, the level of Phe and Tyr was negative correlated with high-density lipoprotein (r=-0,378 and r=-0,543, respectively, p<0,05), and the level of Tyr with LDL (r=0,349, p<0,05). When isolating the group with proven atherosclerosis of peripheral and/or coronary arteries, a statistically significant difference was revealed between the group of patients with CVD and clinical and instrumental signs of atherosclerosis and the group of patients with CVD without proven atherosclerosis in Phe level (p=0,019).Conclusion. Concentrations of AAA were higher in patients with CVD, comparing with the control group. At the same time, an increase of the Phe level was associated with the presence of peripheral or coronary atherosclerosis. The revealed correlations of AAA with EchoCG parameters and lipid spectrum parameters require further study to understand the involvement of AAA in pathogenesis of CVD and its potential role as treatment target.